Strategi Pembelajaran Pendidikan Agama Islam di SMP Global Islamic School Yogyakarta - Roidah Lina (At Turots: Jurnal Pendidikan Islam, 2023)
This research was carried out with the aim of finding out Islamic Religious Education learning strategies at Global Islamic School Middle School. This research was carried out using qualitative descriptive methods with data collection techniques of observation, interviews and documentation. The data processing techniques used in this research are description, reduction and drawing conclusions. The results of this research show that the learning strategies and methods used vary greatly according to the material and subject which can make students become active students. In teaching and learning activities at Global Islamic School Middle School, teachers use two variations of language in learning, namely Indonesian and International Language in the form of using English to prevent and handle boredom in class. PAI learning methods at SMP Global Islamic School vary according to the material and subjects, including reading, discussion, debate, exchanging ideas, practice and presentations. There are also additional programs such as prayer practice, ablution, and reading the Koran with the tajwid laws learned that day. SMP Global Islamic School sets a target for graduates to have memorized juz 30 and recited khatam tadarus/recitations of the Al-Qur'an 30 juz once within 3 years of study.